Remaja dan Kegandrungan Budaya Populer Jepang - Abdul Rahman (Melati Institute, 2023)
After Indonesia's independence, its relationship with Japan thawed. This good relationship is shown by the cultural events that are often held both domestically and abroad. In Indonesia, there are many Japanese cultural events that are popularly known as Japan Pop Culture.J-pop first developed in the 1990s and continues to grow to this day. Manga and anime are examples of two of the most popular J-pop genres in Indonesia, and their popularity has been around for a long time, even ahead of Korean dramas and boy bands. This research seeks to examine the obsession of Makassar teenagers with Japanese Popular Culture, especially manga. This research applies qualitative research methods in which data collection is done by observation and interviews. The results showed that the obsession of Makassar teenagers with Japanese culture cannot be separated from the rapid advancement of information about Japanese culture in the media. For them, learning Japanese culture also brings income and skills.